TREATMENT OF HYDROCARBON FUELS WITH A MAGNETIC FIELD IS A WAY TO INCREASE THE EFFICIENCY AND ENVIRONMENTAL FRIENDLINESS OF POWER UNITS OF TRANSPORT DEVICES - Rumyantsev, Vladislav; Savinov, Viacheslsav (Sworld-Us Conference proceedings, 2023)
An analysis of the operation of automobile internal combustion engines was performed, a technical solution for treating liquid hydrocarbons with magnetic fields was proposed, and a physical result was obtained during the practical operation of automobiles